A Decade of Monitoring an Indo-Pacific Grouper Spawning Aggregation: Benefits of Protection and Importance of Survey Design - Sadovy de Mitcheson, Yvonne; Colin, Patrick L.; Lindfield, Steven J.; Bukurrou, Asap (Frontiers in Marine Science, 2020)
Groupers (Family Epinephelidae) are valuable and vulnerable reef-associated fishes. Medium to large-sized Indo-Pacific genera, such as Epinephelus and Plectropomus, are important in local/international trade, and are particularly susceptible to overfishing due to their economic value, longevity, late maturation and, for some species, aggregation-spawning. Three species, Plectropomus areolatus, Epinephelus polyphekadion, Epinephelus fuscoguttatus, are threatened (IUCN Red List) and, when exploited on their aggregations, typically undergo declines unless managed. To effectively assess spawning aggregation status and identify changes over time following fishing or management, a robust sampling protocol is essential. This was developed and tested at a protected, but previously depleted, spawning site shared by these three species in Palau, western Pacific. Underwater visual census (UVC) tracked changes in fish abundance (numbers) across their aggregation site between 2009 and 2019. Census data on abundance and density were complemented by additional technologies to generate a more complete picture of this aggregation site and the three species, including stationary cameras to monitor fish with divers absent, stereo-video to measure fish lengths, and oceanographic instruments to measure variability in currents and water temperature. Results show that protection outcomes depend on biology and on active enforcement and that UVC survey design must adequately address temporal/spatial variability to effectively document changes in fish abundance. Over the decade-long study, P. areolatus, the fastest-maturing species, showed a near fourfold increase in peak annual abundance (increasing from annual peak numbers of c.450 to 1,800 fish), followed by a more modest increase in E. polyphekadion (increase from c.500 to at least 600 fish and a twofold density increase) and relative stability in the slowest maturing, longest-lived species, E. fuscoguttatus (stable between approximately 300 and 450 fish). The study highlighted need for caution when fish density is used as a proxy for abundance in studies when entire aggregations cannot be surveyed, because the two measures may not be correlated at higher abundances. The results clearly show the need for robust sampling design and that effective protection contributes to recovery of depleted spawning aggregations.